Inter- and intracellular mitochondrial communication: signaling hubs in aging and age-related diseases - Meng Zhang; Jin Wei; Chang He; Liutao Sui; Chucheng Jiao; Xiaoyan Zhu; Xudong Pan (Cellular & Molecular Biology Letters)
Abstract Mitochondria are versatile and complex organelles that can continuously communicate and interact with the cellular milieu. Deregulated communication between mitochondria and host cells/organelles has significant consequences and is an underlying factor of many pathophysiological conditions, including the process of aging. During aging, mitochondria lose function, and mitocellular communication pathways break down; mitochondrial dysfunction interacts with mitochondrial dyscommunication, forming a vicious circle. Therefore, strategies to protect mitochondrial function and promote effective communication of mitochondria can increase healthy lifespan and longevity, which might be a new treatment paradigm for age-related disorders. In this review, we comprehensively discuss the signal transduction mechanisms of inter- and intracellular mitochondrial communication, as well as the interactions between mitochondrial communication and the hallmarks of aging. This review emphasizes the indispensable position of inter- and intracellular mitochondrial communication in the aging process of organisms, which is crucial as the cellular signaling hubs. In addition, we also specifically focus on the status of mitochondria-targeted interventions to provide potential therapeutic targets for age-related diseases. Graphical Abstract